Are Children Smarter (or More Socialized) Because of the Internet? - Thanh Nguyen, Phong; Edwita, Edwita; Bich Huynh, Vy Dang (Opción, 2019)
Presently the internet becomes the most important part of a human life. On the question of children becoming smarter or not because of web can have different opinion by different persons. So in this study it is tried to get the fact that is internet really helpful for a children for being smarter. Some times its seems that the internet is increasing the dependency and the child- hood of children is loosing in the world of internet. The children becomes boys in early age. They are disconnecting them self from the outer world and lack of physical activities is making children lazy and short temper. Although there are many families where internet is only used as facility not like a life line. The parents restrict children only to use the internet when it is really required. Else they are not allowed to use the internet. Rather than playing outdoor games they prefer to play multiplayer games and do not want to do any other work. Even internet and multiplayer games is also disturbing the daily routine of children. So the result is they will not eat on time, the sleep will not proper and rather than being smarter its making the children dumb dependent on internet.